1964
DOI: 10.2134/agronj1964.00021962005600040015x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Lee Soybeans to Different Strains of Rhizobium japonicum1

Abstract: Synopsis In soils free of soybean rhizobia, some strains of Rhizobium japonicum were more effective than others on Lee soybeans. In rhizobia‐contaminated soil, none of the strains caused any detectable growth responses on seed‐inoculated plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 0 publications
3
37
0
Order By: Relevance
“…The highest seed yield was obtained with strain USDA 110. It has been previously reported that this strain has high capacity of N2-fixation which results in increasing the seed yield of soybean (Abel and Erdman, 1964;Sloger, 1969;Vest, 1971).…”
Section: Resultsmentioning
confidence: 92%
“…The highest seed yield was obtained with strain USDA 110. It has been previously reported that this strain has high capacity of N2-fixation which results in increasing the seed yield of soybean (Abel and Erdman, 1964;Sloger, 1969;Vest, 1971).…”
Section: Resultsmentioning
confidence: 92%
“…Two other cheaters that obtained less benefit from symbiosis (light blue upside-down triangles) and three apparently maladapted strains that gained almost no benefit (brown diamonds) are also shown. Data from Abel & Erdman (1964); graphical approach suggested by Ezra Lyon.…”
Section: The Rhizosphere As a Tragic Commonsmentioning
confidence: 99%
“…Figure lb shows the variation in benefit provided to a soybean host cultivar "Lee" from 21 different Bradyrhizobimn japonicum strains as a function of nodule weight per plant (data from Abel & Erdman 1964). Three strains (diamonds) gave litde plant benefit (yield similar to uninoculated controls) but also litde rhizobium benefit (low nodule weight per plant).…”
Section: The Rhizosphere As a Tragic Commonsmentioning
confidence: 99%
“…In the American midwest, symbiotically-superior inoculant strains of Bradyrhizobium japonicum routinely give rise to only 5-20% of the nodules produced on soybeans (Berg et al, 1988;Caldwell and Vest, 1970;Moawad and Schmidt, 1987;Weaver and Frederick, 1974 a,b), and usually fail to improve yield (Abel and Erdman, 1964;Beard and Hoover, 1971;Berg et al, 1988;Caldwell and Vest, 1970;Ham et al, 1971a). This problem has been perceived as one of competition between soil strains and those applied in the inoculant.…”
Section: Introductionmentioning
confidence: 99%
“…This problem has been perceived as one of competition between soil strains and those applied in the inoculant. By contrast, where soils have not been cropped previously to soybean, establishment of the inoculant strains is not a problem, and increases in seed yield following inoculation are common (Abel and Erdman, 1964;Weaver and Frederick, 1974b).…”
Section: Introductionmentioning
confidence: 99%